Mental health in the Family Health Strategy as perceived by health professionals - Jacqueline de Souza; Letícia Yamawaka de Almeida; Margarita Antonia Villar Luis; Andreia Fernanda Nievas; Tatiana Maria Coelho Veloso; Sara Pinto Barbosa; Bianca Cristina Ciccone Giacon; Francine Baltazar Assad
ABSTRACT Objective: to analyze the management of mental health needs in primary care as perceived by Family Health Strategy professionals. Method: this was a qualitative descriptive exploratory study developed within the coverage area of five family health teams. The data were collected using observation, group interviews, individual semi-structured interviews, and focus groups. Content analysis was conducted using text analysis software and interpretation was based on the corresponding analytical structures. Results: numerous and challenging mental health demands occur in this setting, for which the teams identified care resources; however, they also indicated difficulties, especially related to the operationalization and integration of such resources. Conclusion: there is a need for a care network sensitive to mental health demands that are better coordinated and more effectively managed.